Novel potential marker for native anteversion of the proximal femur. Issue 8 (18th October 2016) - Durgin, Chesley F.; Spratley, E. Meade; Satpathy, Jibanananda; Jiranek, William A.; Wayne, Jennifer S.
ABSTRACT: Identifying native femoral version from proximal femoral landmarks would be of benefit both for preoperative assessment as well as intraoperatively. To identify potential markers for femoral anteversion, an empirical framework was developed for orientation‐independent analysis of the proximal femur from pelvic CT to allow for segmentation of the proximal femur into five constituent regions: Femoral head, femoral neck, greater trochanter, lesser trochanter and femoral shaft. The framework is based on the identification of differences in the radius of curvature at anatomic zones of transition between regions of the proximal femur, followed by non‐linear geometric shape fitting. The framework is applied to 86 proximal femurs segmented from pelvic CTs, with at least 2 cm of proximal femur remaining below the lesser trochanter, obtained for non‐musculoskeletal pathology to investigate potential proximal femoral markers for native femoral version. The analysis of the proximal femur suggests a fixed relationship between the maximal femoral canal diameter 1 cm proximal to the base of the lesser trochanter from the center of the greater trochanter and the femoral neck axis of 4.13° +/− 4.99°. Further full‐length femoral studies are needed to confirm the relationship of the maximal canal diameter as a proxy for native femoral anteversion. Published by Wiley Periodicals, Inc. J Orthop Res 35:1724–1731, 2017. Abstract : Identifying native femoral version from proximal landmarks would benefit preoperative and intraoperative assessment. An empirical framework was developed for orientation‐independent analysis of the proximal femur from CTs. Eighty six proximal femurs were analyzed which suggested a fixed relationship between the maximal femoral canal diameter 1 cm proximal to the lesser trochanter from the center of the greater trochanter and the femoral neck axis of 4.13° +/− 4.99°. Further studies need to confirm this relationship as a proxy for native femoral anteversion.